solve the equation for t. -5(t-5)+9t=6t-4solve the equation for t. -5(t-5)+9t=6t-4

Question

solve the equation for t. -5(t-5)+9t=6t-4solve the equation for t. -5(t-5)+9t=6t-4

in progress 0
Kennedy 2 weeks 2022-01-10T13:29:50+00:00 1 Answer 0 views 0

Answers ( )

    0
    2022-01-10T13:31:07+00:00

    Answer:

    t = 29/2

    Step-by-step explanation:

    -5(t – 5) + 9t = 6t – 4

    -5t + 25 + 9t = 6t – 4

    4t + 25 = 6t – 4

    4t + 29 = 6t

    29 = 2t

    29/2 = t

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )